Low temperature hydrogenation of α-angelica lactone on silica supported Pd–NiO catalysts with synergistic effect. Issue 70 (11th July 2016) - Zhang, Pei; Yuan, Qingqing; Chen, Li; Xue, Teng; Guan, Yejun; Wu, Peng
Abstract : Low temperature (30 °C) hydrogenation of α-angelica lactone under 0.3–1 MPa H2 with very high activity is achieved by loading a minute amount (0.2 wt%) of Pd nanoparticles on NiO. Abstract : The hydrogenation of α-angelica lactone (α-AL) was achieved under mild conditions on silica supported Pd–NiO catalysts. NiO and palladium were sequentially loaded on silica by wet-impregnation and deposition–reduction, respectively. First a series of NiO/SiO2 supports with varying Ni contents were prepared by a wet-impregnation method with Ni(NO3 )2 as the precursor followed by calcination in air. Then a minute amount of palladium (0.2 wt%) was loaded by a deposition–reduction method using NaBH4 as a reducing reagent. The Pd–NiO catalysts were characterized by nitrogen adsorption, XRD, H2 -TPR, XPS and TEM. The NiO were heterogeneously dispersed on silica with particle sizes ranging from 10 to 50 nm, whereas Pd was finely loaded with a diameter less than 5 nm. Nanoscale intimacy between Pd and NiO was noticed by HRTEM, resulting in high catalytic activity in liquid phase hydrogenation of α-angelica lactone to γ-valero lactone (GVL) under mild conditions. 0.2Pd–9.9NiO/SiO2 showed the best activity among all the catalysts investigated, with 82% conversion and 100% selectivity to GVL within several minutes at 30 °C and 0.3–1 MPa H2 pressure.